Synthesis of LiFePO4 Nanocomposite with Surface Conductive Phase by Zr Doping with Li Excess for Fast Discharging. Issue 2 (5th February 2019) - Li, Yuanchao; Zhang, Yuping; Ma, Jingjing; Yang, Li; Li, Xiaobo; Zhao, Erqing; Fan, Shumin; Xu, Guangri; Yang, Shuting; Yang, Changchun
Abstract : Surface phase with ion or electron conductor is essential for the improved rate capability of mostly electronically insulating LiFePO4 materials with only one-dimensional Li + transport. Here, a surface conductive phase, created through Zr 4+ doping in Li-excess LiFePO4, forms synergy with carbon coating layer to facilitate electron transportation, which greatly improved rate performance of LiFePO4 materials. The LiFePO4 with appropriate amount of surface conductive phase exhibits excellent rate capability with 125 mA·h·g −1 at 20 C and stable capacity retention with 98.5% for 200 cycles at 5 C. The finding provides a new idea for improved electrochemical performances of LiFePO4 materials and contributes to the scaled-up production of LiFePO4 materials for a low-cost route.